PRE-SERVICE TEACHER EDUCATION: EXPERIENCE AND DEVELOPMENTAL TENDENCIES AT LIEPAJA UNIVERSITY - Samusevica, Alida; Striguna, Santa (European Scientific Journal, ESJ, 2014)
Constant upgrade of professional teacher education is a staple resource for boosting the general quality of education in any country. For this reason, seeking appropriate ways to achieve the said upgrade and appraising potential resources that might serve this purpose is an ever-present hot topic in the field of educational research. In keeping with this popular trend, the present study analyses university students’ views on key features of an ideal teacher’s professional practice that successfully meets the challenges of modern-day knowledge society. Meanwhile, in-service teachers’ reflection on their actual professional practice is examined for expert insights and used to formulate recommendations for upgrading the pedagogical education that is offered in teacher education programmes at Liepaja University. The paper highlights the need for a refined model of collegial university-school partnership that would support optimal socialisation of novice teachers and contribute to pre-service teachers’ pedagogical competence.